KARAKTERISASI AKTIVITAS ANTIMIKROBA BEBERAPA ASAM LEMAK ASKORBIL - Elidar Naiola (BERITA BIOLOGI, 1999)
The study is directed t investigate the antimicrobial activity f six ascorbyl fatty acids. The minimum concentrations were observed in ascorbyl caprate and ascorbyl laurate. Ascorbyl caprate was the strongest ester with the minimum inhibitory concentration (1,25-5 nM). Among microorganisms tested,S. cerevisiae was more senseitive than others. The sensitivity of S. cerevisiae was depending on the strains and S.cerevisiae OUT7054 was the most sensitive strain to the ascorbyl caprate which was the sterilizing agent rather than microbiostic agent.The antimicrobial activity of ascorbyl caprate was infuenced remarkably by temperature and pH.The most effective conditbns for sierilizatin of yeast were higher temperature and low pH.